Reconstruction of E-Module of Circular Motion Based Guided Inquiry - Suci Prihatiningtyas; Siti Alimah (SEJ (Science Education Journal), 2021)
This study aims to determine the feasibility of the E-Module Circular Motion Based Guided Inquiry. This research is a research development or Research and Development (R&D) with the ADDIE model. The research instrument used was a validation sheet by the validator and student response questionnaires. The results of the validation sheet and student response questionnaires were assessed based on the Likert scale. The results of data analysis from the validation results of the E-Module Circular Motion Based on Guided Inquiry obtained a percentage of 92,02%. This shows that in general the E-Module Circular Motion Based on Guided Inquiry that was developed is very feasible to be used in learning circular motion material in class X SMK. E-Module Circular Motion Based on Guided Inquiry is a medium that can attract the attention of students.